-3x+6=-2(3x+6)

Simple and best practice solution for -3x+6=-2(3x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+6=-2(3x+6) equation:


Simplifying
-3x + 6 = -2(3x + 6)

Reorder the terms:
6 + -3x = -2(3x + 6)

Reorder the terms:
6 + -3x = -2(6 + 3x)
6 + -3x = (6 * -2 + 3x * -2)
6 + -3x = (-12 + -6x)

Solving
6 + -3x = -12 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
6 + -3x + 6x = -12 + -6x + 6x

Combine like terms: -3x + 6x = 3x
6 + 3x = -12 + -6x + 6x

Combine like terms: -6x + 6x = 0
6 + 3x = -12 + 0
6 + 3x = -12

Add '-6' to each side of the equation.
6 + -6 + 3x = -12 + -6

Combine like terms: 6 + -6 = 0
0 + 3x = -12 + -6
3x = -12 + -6

Combine like terms: -12 + -6 = -18
3x = -18

Divide each side by '3'.
x = -6

Simplifying
x = -6

See similar equations:

| -3(5y-7)+2(4y+6)= | | 6(2x-4)=36 | | 5x-(3x-4)=17 | | 4x^2-28x+11=0 | | 6(13-2x)=50-x+46 | | 0+11y=7 | | 0+11y=y | | 2(4x+3)=12x+4-4x+2 | | 3(2x-1)+2(x+3)=3(x-2)-2(x-1) | | x^2-13x+24=0 | | 12x-7=1+10x | | -7=-y+4 | | x+(x-3007)=7803 | | X=0+4 | | 250=84-5(x-4) | | 5+8q=7+7q | | -5y-3=1-6y | | X^2+x+0.21=0 | | 4(x-2)=x-8+3x | | 12x+6-10x=2x+6 | | (n-2)*5=20 | | 22a+5-(a-7)=48 | | x(x-2)+(x-2)(x+2)=0 | | 2-.75k=.125k+9 | | 4(x+2)=5-(x+2) | | 10(9c-1)-14=88c+10 | | 3x+-3+5=5 | | 4(x+2)=5-(x-2) | | 0.6(x-2)=12.0 | | 8x+8-5x=3x+8 | | 7n=77 | | 12x-3=90+3(x-7) |

Equations solver categories